2016
DOI: 10.1002/aoc.3430
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot self‐assembly and photoreduction synthesis of silver nanoparticle‐decorated reduced graphene oxide/MIL‐125(Ti) photocatalyst with improved visible light photocatalytic activity

Abstract: e In recent years, tremendous research efforts have been made towards developing metal-organic framework (MOF)-based composites for photocatalytic applications. In this work, bipyramid-like MIL-125(Ti) frustum enwrapped with reduced graphene oxide (rGO) and dispersed silver nanoparticles (Ag NPs) was fabricated using an efficient one-pot self-assembly and photoreduction strategy. The as-obtained materials were characterized using field emission scanning electron microscopy, transmission electron microscopy, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(55 citation statements)
references
References 42 publications
(58 reference statements)
0
55
0
Order By: Relevance
“…Concurrently, the Ti 2 p , C 1s, N 1s, and O 1s XPS spectra of Ti‐MOF‐NH 2 are illustrated in Figure S3 . High‐resolution XPS spectrum of the Ti 2 p ( Figure S3a ) electrons and binding energies of Ti 2 p 3/2 and Ti 2 p 1/2 peaks were located at 458.7 and 464.5 eV, respectively, indicating that the titanium bound to oxygen remained in oxidation state IV for the titanium‐oxo cluster . Figure S3b demonstrated that the high‐resolution XPS spectrum of C 1s was the same as that of the Fe‐MOF‐NH 2 , of which the four C–C/C–H, C–N, N–C=O, and –COO groups were found.…”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, the Ti 2 p , C 1s, N 1s, and O 1s XPS spectra of Ti‐MOF‐NH 2 are illustrated in Figure S3 . High‐resolution XPS spectrum of the Ti 2 p ( Figure S3a ) electrons and binding energies of Ti 2 p 3/2 and Ti 2 p 1/2 peaks were located at 458.7 and 464.5 eV, respectively, indicating that the titanium bound to oxygen remained in oxidation state IV for the titanium‐oxo cluster . Figure S3b demonstrated that the high‐resolution XPS spectrum of C 1s was the same as that of the Fe‐MOF‐NH 2 , of which the four C–C/C–H, C–N, N–C=O, and –COO groups were found.…”
Section: Resultsmentioning
confidence: 99%
“…MOFs have many excellent properties that are different from those of traditional porous and crystal materials, such as nanoscale controlled pore structure, high surface area, and metal-organic ligand combination diversity, etc. Correspondingly, MOF has a variety of potential applications in many fields, including gas separation and storage, [1][2][3][4] catalysis, [5][6][7] biochemistry 8 and so on. Especially, many investigations have demonstrated that MOF materials are promising catalysts in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, many investigations have demonstrated that MOF materials are promising catalysts in photocatalysis. 5,6,[9][10][11][12][13][14][15][16] As one of the most popular MOF, 1,[5][6][7] the titanium-based MIL-125 can catalyze the oxidation of alcohols to aldehydes under the UV irradiation, indicating that MIL-125 is an active photocatalyst. 10 However, because of the large optical band gap (3.6 eV), 10 MIL-125 is only active under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it is imperative to develop efficient visible-light photocatalysts. Based on this, as is currently required, many visible-light photocatalysts have emerged, such as BiVO 4 [6], g-C 3 N 4 [7,8], BiOI [9], Ag 3 VO 4 [10], Ag 3 PO 4 [11] and graphene-based materials [12,13].…”
Section: Introductionmentioning
confidence: 99%